Personal, Political, Professional: A Practice in Transition - Wallace, Niki (Journal of Management Policy and Practice, 2019)
It is widely agreed that in order to contribute to transitions towards sustainability, design and its practitioners must also transition. This paper presents findings from the first two years of transition in my design practice. The paper explores what has been required of me personally, politically, and professionally, and draws on projects from my PhD. Using a critical pragmatism to examine my practice’s transition from ‘making greener things’ towards ‘design for transitions’, the paper explores how slower approaches such as transition design and autonomous design can extend the political reach of a design practice and discusses how this transpires.